Kepuasan Kerja Dipengaruhi Oleh Motivasi Kerja, Disiplin Kerja, Dan Lingkungan Kerja Pada Pegawai Dinas Kependudukan Dan Pencatatan Sipil (Disdukcapil) Kota Balikpapan - Pebriana, Wiwin; Hadiyatno, Didik; Cipto, Rahajeng Cahyaning Putri (Jurnal Bisnis dan Kewirausahaan, 2024)
The Balikpapan City Population and Civil Registration Office must certainly serve the community well. The provision of good service is certainly inseparable from skilled and reliable human resources. This quantitative research aims to analyze the influence of work motivation, work discipline, and work environment on job satisfaction of employees of the Population and Civil Registration Office of Balikpapan City, using a purposive sampling technique totaling 40 employees of the Population and Civil Registration Office of Balikpapan City. Data collection in this study was done by distributing questionnaires and using SmartPLS in processing the data. The results of the study show that work motivation and work environment have a positive and significant influence on the job satisfaction of employees of the Balikpapan City Population and Civil Registration Office, while work discipline has a negative and insignificant effect on the job satisfaction of employees of the Balikpapan City Population and Civil Registration Office.